Transcriptome Reprogramming of CD11b(+) Bone Marrow Cells by Pancreatic Cancer Extracellular Vesicles - Maia, Joana (2021)
Funding: JM was supported by “Fundação para a Ciência e a Tecnologia” (PD/BD/105866/2014). This work was supported by the Champalimaud Foundation; grant 751547 from H2020-MSCAIF-2016; EMBO Installation Grant 3921; grant 2017NovPCC1058 from Breast Cancer Now’s Catalyst Programme, which is supported by funding from Pfizer; grant 765492 from H2020-MSCA-ITN-2017; and grant LCF/PR/HR19/52160014 from “La Caixa” Foundation. This work was also funded by FEDER funds through the Operational Programme for Competitiveness Factors-COMPETE and National Funds through the Foundation for Science and Technology (FCT), under the project: PTDC/MED-ONC/28489/2017 (to AM). JP acknowledges the FCT grant SFRH/BD/137319/2018.